2011
DOI: 10.1093/tropej/fmr074
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of HIV/AIDS Prevention and Factors Associated with Condom Use Among Adolescents in Northeast Brazil

Abstract: The knowledge regarding HIV/AIDS prevention was satisfactory. However, this does not imply that adolescents put such knowledge to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Older adolescents were more likely to be aware of HIV and to be tested for HIV. This finding is in line with a study conducted in Brazil where younger adolescents were less knowledgeable about HIV than older ones . For adolescents, the probability of knowledge about HIV increases with age, which may related to more opportunities for testing for middle‐ and later‐aged adolescents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Older adolescents were more likely to be aware of HIV and to be tested for HIV. This finding is in line with a study conducted in Brazil where younger adolescents were less knowledgeable about HIV than older ones . For adolescents, the probability of knowledge about HIV increases with age, which may related to more opportunities for testing for middle‐ and later‐aged adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…This community‐based cross‐sectional study was conducted in the Kersa (rural) and Harar (urban) Health Demographic Surveillance System (HDSS) sites in eastern Ethiopia from 1 February 2016 to 30 March 2016. The Kersa HDSS is comprised of 12 kebeles (sub‐districts; the smallest administrative units) and has been under surveillance since its establishment in 2007 . The Harar HDSS is comprised of six kebeles and has been under surveillance since its establishment in 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is inconsistent with a number of studies. An analysis of Demographic health survey of Uganda reported older girls to likely have good knowledge of HIV (Twinomugisha Fred, 2019).Moreover a study conducted in North East Brazil also reported younger adolescents to be having less knowledge of HIV than older adolescents (da Marinho et al, 2012).…”
Section: Factors Associated With Knowledge On Hivmentioning
confidence: 99%